On Ćirić-Prešić Operators in Metric Spaces. (31st July 2021) - Boonsri, Narongsuk; Saejung, Satit; Sitthikul, Kittipong
Abstract : We show that the Prešić type operators of several variables can be regarded as an operator of a single variable and the fixed point problem of Prešić type can be regarded as a classical fixed point problem. We extend the recent result of Ćirić and Prešić by using the classical approach of Prešić. The key of the proof is based on the mappings introduced by Kada, Suzuki, and Takahashi. We also discuss the convergence problems of recursive real sequences and the Volterra integral equations as an application of our result.